PENERAPAN DESAIN RIAS FANTASI MENGGUNAKAN SOFTWARE ANSERIES DENGAN SUMBER IDE BUNGA MATAHARI (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
PENERAPAN DESAIN RIAS FANTASI MENGGUNAKAN SOFTWARE ANSERIES DENGAN SUMBER IDE BUNGA MATAHARI Kristin Muktiana1,a) dan Erna Setyowati2,b) Mahasiswa Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, Gedung E10 Lt 2 Kampus Sekaran, Gunungpati, Semarang 50229 Correspondingauthor:a)kristinmuktiana28@gmail.comb)ernasetyowati@mail.unnes.ac.id Abstract. The application of fantasy makeup design using Anseries software in this study was to facilitate the process of making fantasy makeup design. Research objectives: (1) To determine the validity of fantasy makeup design with sunflower sources using Anseries software. (2) To find out the results of fantasy makeup design with sunflower sources. This study used an experimental method with one-group pretest-posttest design. The research object was Anseries software. The research subjects consisted of three expert validators and 15 moderate-trained panelists from two different study programs in Universitas Negeri Semarang. The data collection techniques were using interviews, observation, and documentation. The data analysis was using descriptive percentage. The fantasy makeup design was using Anseries software which has 4 designs, namely the design of the face, chest, arms and legs. The results of the descriptive analysis showed that the product of fantasy makeup design was declared very valid by three validators based on the assessment indicators of form, color, ease of application, and final result. The products of fantasy makeup design using Anseries software have been declared